Pengaruh Kompilasi Terapi Al-Qur'an dan Shaping Modifikasi Perilaku untuk Menurunkan Gejala Obsessive Compulsive Disorder Type Washer di Griya Sehat AT TIN Surabaya - Siregar, Halimatus Sa'diyah; Affandi, Ghozali Rusyid (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Obsessive Compulsive Disorder (OCD) is a mental disorder characterized by the presence of obsessions (unwanted and intrusive thoughts) and compulsions (repetitive behaviors performed to reduce the anxiety or discomfort caused by those obsessions), which significantly interfere with an individual's daily life. The combination of Qur’anic Therapy and Shaping Behavioral Modification techniques is often employed to address this disorder. This study aims to investigate the effectiveness of the compiled Qur’anic Therapy and Shaping Behavioral Modification in reducing symptoms of Obsessive Compulsive Disorder (OCD), specifically the Washer Type. The research employs a quantitative approach with a quasi-experimental single-subject design using an interrupted time series design. The study applies an A-B-A design model. The subject was selected using purposive sampling, and data were collected through systematic observation. The data analysis was conducted using visual graph analysis across two stages: within-condition and between-condition comparisons. Data collection in the first baseline condition (A1) was conducted through seven observation sessions. This was followed by the intervention phase (B), in which the compiled Qur’anic Therapy and Shaping Behavioral Modification were implemented over thirteen observation sessions. The study concluded with a second baseline condition (A2), observed over another seven sessions. Based on the visual data analysis, both within and across conditions, the compiled Qur’anic Therapy and Shaping Behavioral Modification effectively reduced the symptoms of Obsessive Compulsive Disorder, Washer Type. Furthermore, this combination of therapeutic techniques not only alleviated anxiety but also contributed to the positive transformation of habits and behaviors, indicating broader benefits for psychological and behavioral well-being.